2018
DOI: 10.1038/s41598-018-19930-w
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial biogenesis and metabolic hyperactivation limits the application of MTT assay in the estimation of radiation induced growth inhibition

Abstract: Metabolic viability based high throughput assays like MTT and MTS are widely used in assessing the cell viability. However, alteration in both mitochondrial content and metabolism can influence the metabolic viability of cells and radiation is a potential mitochondrial biogenesis inducer. Therefore, we tested if MTT assay is a true measure of radiation induced cell death in widely used cell lines. Radiation induced cellular growth inhibition was performed by enumerating cell numbers and metabolic viability usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
151
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 241 publications
(173 citation statements)
references
References 39 publications
5
151
0
1
Order By: Relevance
“…Several studies have shown that E2 has the ability to increase mitochondrial function and biogenesis (reviewed in [42]), therefore, we explored whethe Sirt3 plays a role in E2-induced metabolic fitness of MCF-7 cells. As observed in Figure 3A,C, Sirt3 potentiated this inducing effect of E2 leading to increased metabolic activity, primarily as a result of the induced rise in SDH-A expression ( Figure 3B) [26]. This is not surprising, considering that ERα is an essential estrogen receptor for most E2-mediated increases in respiratory chain proteins and antioxidant enzymes [43,44].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Several studies have shown that E2 has the ability to increase mitochondrial function and biogenesis (reviewed in [42]), therefore, we explored whethe Sirt3 plays a role in E2-induced metabolic fitness of MCF-7 cells. As observed in Figure 3A,C, Sirt3 potentiated this inducing effect of E2 leading to increased metabolic activity, primarily as a result of the induced rise in SDH-A expression ( Figure 3B) [26]. This is not surprising, considering that ERα is an essential estrogen receptor for most E2-mediated increases in respiratory chain proteins and antioxidant enzymes [43,44].…”
Section: Discussionsupporting
confidence: 56%
“…First, we tested the effect of E2 and Sirt3 on metabolic activity of MCF-7 cells using MTT assay. The MTT salt is reduced to formazan in the metabolically active cells predominantly by mitochondrial complex-II subunit succinate dehydrogenase A (SDH-A) and is considered to be a marker of metabolic potential of the cell [26]. The Sirt3-overexpressing cells had significantly higher basal metabolic activity (p < 0.001) and Sirt3 further enhanced the inducing effect of E2 ( Figure 3A), while ICI effectively abolished E2-induced metabolic activity to control levels in both cell lines.…”
Section: Sirt3 Amplifies E2-induced Metabolic Activity and Mitochondrmentioning
confidence: 99%
“…The fourth Cell passage were used in this study. During passaging, fibroblasts were transported from flask to another flask with trypsenization process using Trypsin EDTA solution aiming to de-adhering cells from the flask (11,12) .…”
Section: Methodsmentioning
confidence: 99%
“…Once the fibroblast cultures were found at 80-90% confluence, they were separated from the flask with trypsin-EDTA. Then 5×10 4 cells were overlaid in 100 µL of culture medium onto insert culture plates and incubated for 5h period at 99F, 6% CO 2 , and 97% humidity (12) . Initially, the complete media was added without material extract, to allow adaptation of the cells to the plate for 24h.…”
Section: Classification Of the Samplementioning
confidence: 99%
See 1 more Smart Citation